2020
DOI: 10.1111/jac.12475
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the combined effects of air temperature and relative humidity on water‐use efficiency of barley under drought stress

Abstract: As soil water deficit limits crop growth and yield, yet the combined effects of soil drying and elevated vapour pressure deficit (VPD) of the air on crop performance have not been fully understood. The objective of this study was to investigate the interactive effects of soil drying and elevated VPD on growth and physiology of barley seedlings grown under controlled climates. The plants were grown in four separate climate chambers with two air temperature (T, 20 and 30°C) and relative humidity (RH: 60 and 75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…S7). Reduced g s and photosynthesis due to high VPD can happen in well-irrigated plants with high temperatures impacting enzymatic activity and increasing photorespiration above a specific threshold (Zhang et al, 2021). More recently, Schönbeck et al (2022) also showed that high VPD induced loss of xylem conductivity in well-irrigated plants, suggesting that reduced photosynthesis as a response to high VPD and temperature could prevent xylem embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). Reduced g s and photosynthesis due to high VPD can happen in well-irrigated plants with high temperatures impacting enzymatic activity and increasing photorespiration above a specific threshold (Zhang et al, 2021). More recently, Schönbeck et al (2022) also showed that high VPD induced loss of xylem conductivity in well-irrigated plants, suggesting that reduced photosynthesis as a response to high VPD and temperature could prevent xylem embolism.…”
Section: Discussionmentioning
confidence: 99%
“…S7). Reduced g s and photosynthesis due to high VPD can happen in well‐irrigated plants with high temperatures impacting enzymatic activity and increasing photorespiration above a specific threshold (Zhang et al ., 2021). More recently, Schönbeck et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high air relative humidity will alleviate partly this negative impact by decreasing VPD (Grossiord et al ., 2020). Therefore, the overall impact depends on the tradeoffs between the effects of high dry bulb temperature and high humidity on crop productivity (Grossiord et al ., 2020; Zhang et al ., 2021a). Moreover, how deadly humid heatwaves will impact the diversity and conservation of crop species still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…During deadly humid heatwaves, extreme high temperature results in high vapour pressure deficit (VPD), which reduce crop yield by increasing leaf transpiration and decreasing photosynthetic water‐use efficiency (Rashid et al ., 2018; Zhang et al ., 2021a). On the other hand, high air relative humidity will alleviate partly this negative impact by decreasing VPD (Grossiord et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the transpiration rate response to soil drying is exacerbated by increasing VPD (meaning that plants would decrease the transpiration rate at relatively higher soil moisture levels if the VPD is high; e.g. Devi and Reddy, 2020 ; P. Zhang et al , 2021 , 2022 ). These results are easily predicted using the water demand–supply framework, as that implemented in Wankmüller and Carminati (2022) , and illustrated in Fig.…”
Section: Synthesis: Combined Response To High Vapor Pressure Deficit ...mentioning
confidence: 99%